(3fTGW UOhQ Cgd GdYQaGfs - (3eMeO Hf SdjeGf Hf SYO Hf eSYhO GdcGajLj GdQhej GdMfaj, eMjj GdOjf, CHh YHO Gddg, J (B879 (3g` s
(3ChdgG (B:s
(3hHYO aCbhd gPg eSGFd YXGe , hgj ef CLd GdfYe GdLSGe dbO ef Gddg YR hLd Ydi SdjeGf Ydjg GdSdGe HJagje eSFdI hGMOI CjGg s
(3BNQgG (B:s
(3adfcJa HgPG GdbOQ GdjSjQ ef GdJHjGf, hGdfSeI fTGW UOhQ Cgd GdYQaGf hPdc cdg EfeG gh HaVd Gddg GdcQje s
(3GdfSNI HgG MhGTs
(3eNWhW fGOQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B150s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJhMjO hGdedd hGdfMds